Workplace Bullying among Offshore Workers of an Oil and Gas Company - Kamto, Kamto; Nasri, Sjahrul Meizar; Erwandi, Dadan; Lestari, Fatma; Kadir, Abdul (Unnes Journal of Public Health, 2022)
Workplace bullying has become a psychosocial hazard that will decrease the performance of workers and will ultimately decrease the performance of the company's organization. This study was conducted to look into the correlation between bullying, psychological distress, and satisfaction with life. Respondents involved are offshore workers of an oil and gas company (N = 206) from various entities which are divided into permanent and contract workers, as well as into staff and non-staff positions, who were recruited using the snowball sampling method. Statistical analysis was performed using Pearson correlation test with the SPSS software. Statistical test results showed a significant association between bullying and psychological distress (r permanent=0.658, r contract=0.460, r staff=0.641, and r non-staff=0.453, p =0.001) and satisfaction with life (r permanent=-0.272, r contract=-0.232, r staff=-0.396, and r non-staff=-0.179, p =0.01). From the analysis, it was concluded that permanent workers and staff position have a higher level of psychological distress than contract workers and non-staff, yet they also have a higher level of satisfaction with life. This finding shows the presence of a mediating factor that underlies the fact that although the stress level is higher, the level of satisfaction with life remains higher among these workers. Thus, in-depth research on this phenomenon would be needed.